2016
DOI: 10.1186/s13638-016-0773-3
|View full text |Cite
|
Sign up to set email alerts
|

How network monitoring and reinforcement learning can improve tcp fairness in wireless multi-hop networks

Abstract: Wireless mesh network (WMN) is an emerging technology for the last-mile Internet access. Despite extensive research and the commercial implementations of WMNs, there are still serious fairness issues in the transport layer, where the transmission control protocol (TCP) favors flows with a smaller number of hops to flows with a larger number of hops. TCP unfair behavior is a known anomaly over WMN that attracts much attention in recent years and is the focus of this paper. In this article, we propose a distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Leung [6] propose a distributed mechanism that observes the unfairness in resource allocation and then tunes the TCP parameters accordingly. In their solution, each TCP source models the state of the multi-hop network as an MDP, and then they use the Q-learning algorithm to monitor and learn the transition matrix of the proposed MDP.…”
Section: Implementations Of Fair-rl For Non-societal Fairnessmentioning
confidence: 99%
“…Leung [6] propose a distributed mechanism that observes the unfairness in resource allocation and then tunes the TCP parameters accordingly. In their solution, each TCP source models the state of the multi-hop network as an MDP, and then they use the Q-learning algorithm to monitor and learn the transition matrix of the proposed MDP.…”
Section: Implementations Of Fair-rl For Non-societal Fairnessmentioning
confidence: 99%
“…Studying effect of network parameters on its performance SVM [14] Fairness improvement Striving to balance user experience among users MDP [15] III. APPLICATIONS OF ML FOR NETWORK MANAGEMENT IN WMNS When maintaining a WMN, it is critical to pay attention to certain management-level issues that may compromise the security, integrity or the expected performance level of the system.…”
Section: Detecting and Alerting Users About Possible Attacksmentioning
confidence: 99%
“…However, the fundamental differences between wireless and wired mediums result in substandard performance of TCP over wireless networksespecially affecting TCP unfairness-as TCP favors flows with smaller number of hops in WMNs. To tackle this problem, authors of [15] suggested an approach where each TCP source models the state of the system as an MDP and uses Q-learning to learn the transition probabilities of the proposed MDP based on the observed variables. To maximize TCP fairness, each node hosting a TCP source takes actions according to the recommendations of the Q-learning algorithm and adjusts TCP parameters autonomously.…”
Section: Support Vector Machines (Svms)mentioning
confidence: 99%
“…Despite their influence on the real world, automated decision-making systems have come under scrutiny for potentially unfair outcomes between sub-groups separated based on protected data attributes, such as race, gender, and marital status [7,11,18,22,24,43]. The concept of fairness is applicable more broadly, including technical settings such as fair resource allocation in computer networks [3] and fair task assignment in crowdsourcing [6].…”
Section: Introductionmentioning
confidence: 99%